Though this be madness: A game-theoretic perspective on the Brexit negotiations - Athanassios Pitsoulis; Soeren Schwuchow (ZBW - Leibniz-Informationszentrum Wirtschaft, 2018)
On June 19, 2017 the European Union and the British government officially commenced negotiations on the terms of the British exit from the union. The dominant view among most economic policy analysts and commentators seems to be that the cards are clearly stacked against Britain and that the high-handed behaviour of the British representatives is, at best, either a bluff or, at worst, a sign of a loss of reality. In this paper we develop a formal model to show how this uncertainty regarding the preferences and strategy of the British side may affect the dynamic of the negotiations and may lead to unanticipated outcomes.
Keywords: D78; E65; H12; 330; Brexit; game theory; madman strategy; trembling-hand perfection